Symptom correlations of organic brain impairment and psychopathology in patients with residual schizophrenia - Safonov, D. N.; Сафонов, Дмитро Миколайович (My University, 2020)
Relevance. Organic brain impairment (OBI) is one of the most well studied comorbid pathology to schizophrenia. Nevertheless it is not clear yet, how it influences some structural and dynamic aspects of main pathology, such as positive symptoms variability and intensity or negative symptoms progression. Aim – to analyze influence of most common types of organic brain impairment and intensity of residual schizophrenia symptoms. Materials and methods. A study was performed on 100 case histories of patients of Zaporozhye Regional Clinical Psychiatric Hospital who were treated as inpatients with diagnosis of recurrent schizophrenia (ICD-10:F20.5) in time period from 2010 to 2020.
Keywords: schizophrenia; behavioral representation; organic brain impairment; cerebrovascular catastrophe; symptom intensity